2017
DOI: 10.1016/j.cjca.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Cardiovascular Society and Canadian Pediatric Cardiology Association Position Statement on the Approach to Syncope in the Pediatric Patient

Abstract: Pediatric syncope is a common problem that peaks in adolescence, for which there are few data or evidence-based consensus on investigation and management. This document offers guidance for practical evaluation/management of pediatric patients (age < 19 years) with syncope encountered in the acute or primary care setting. The writing committee used the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) methodology. Most syncope is vasovagal, which is benign and does not require extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 31 publications
0
30
0
3
Order By: Relevance
“…Pacemaker therapy should be considered carefully. For recurrent syncope accompanied by a long cardiac arrest (>4 s), a pacemaker should be considered under the advice of pediatric cardiovascular specialists [41,42] (IIa; C).…”
Section: Pacemaker Therapymentioning
confidence: 99%
“…Pacemaker therapy should be considered carefully. For recurrent syncope accompanied by a long cardiac arrest (>4 s), a pacemaker should be considered under the advice of pediatric cardiovascular specialists [41,42] (IIa; C).…”
Section: Pacemaker Therapymentioning
confidence: 99%
“…The most informative diagnostic test is an accurate, detailed history, ideally from the patient. 1 Confirming typical triggers 2 for the syncope is reassuring and implies a benign prognosis. Recurrence is predicted primarily by the frequency of recent syncopal episodes.…”
Section: Introductionmentioning
confidence: 99%
“…Syncope is common, occurring in approximately 30%–40% of the population by age 60 years. 1 Reflex syncope presents as loss of consciousness and postural tone with spontaneous recovery. The ultimate cause is cerebral hypoperfusion, although the underlying mechanism(s) is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that ECGs are not necessary for diagnosing cardiac causes of syncope; only five of 480 pediatric patients with syncope were found to have a cardiac cause. [ 7 ] Similar to chest pain, a detailed history and physical examination without an ECG are sufficient to determine if syncope can be diagnosed as vasovagal or requires follow-up with a cardiologist or neurologist. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Similar to chest pain, a detailed history and physical examination without an ECG are sufficient to determine if syncope can be diagnosed as vasovagal or requires follow-up with a cardiologist or neurologist. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%